Physicochemical Properties and Storage Stability of Restructured Products Prepared from Mantis Shrimp at Refrigerated Temperature (4±1°C) - Varsha, D.; Balange, A. K.; Layana, P.; Deepitha, R. P.; Iburahim, D. Abuthagir; Joshi, S. A.; Gore, S. B. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted from January to August, 2023 at Central Institute of Fisheries Education, Mumbai, Maharashtra, India, to evaluate nutritionally rich restructured fish products, such as sausages, using mantis shrimp (Miyakella nepa). Ground mantis shrimp meat was incorporated at varying ratios (30%, 50%, and 70%) to replace Pangas fish mince in the restructured fish product. Optimization of the 50% inclusion of shrimp meat in the products was based on physicochemical, rheological, and sensory characteristics, as well as overall acceptability. The optimized restructured fish product in the form of sausages was assessed for quality characteristics over 40 days of refrigerated storage, with a control product containing 100% Pangas mince. Physicochemical parameters did not show significant differences (p>0.05) during refrigerated storage. A reduction in gel strength, coupled with increased lipid oxidation, was observed in the products prepared with mantis shrimp meat throughout the storage period. The whiteness of the products decreased slightly, likely due to the spice mix and protein interactions. SDS-PAGE analysis showed no significant changes in protein patterns. However, the mantis shrimp-incorporated sample received a lower overall acceptability score due to the development of a pungent odor by the end of the 40-day storage period.Overall, the study highlighted limited potential for using mantis shrimp in the development of restructured fish products, particularly with fish of high fat content.